Specially Wettable Membranes for Oil–Water Separation. Issue 23 (27th September 2018) - Wei, Yibin; Qi, Hong; Gong, Xiao; Zhao, Shuaifei
Abstract: The oil–water separation has attracted heightened attention because of the ever‐increasing amounts of oily water produced from the daily activities of humans and industrial processes. Membrane technology as an advanced water purification approach has offered an indispensable option due to its cost‐effective, energy‐efficient, and easy‐to‐operate characteristics. However, traditional membrane materials suffer from severe fouling, which counteracts the superiority of applying membranes in oil–water separation applications. Thanks to the emerging bioinspired interface research, a series of special wettability not only endows membrane surfaces with outstanding antifouling properties but also breaks though the long‐standing tradeoff effect between membrane permeability and selectivity. In this review, the recent advances of membranes used for oil–water separation with special wettability and perspectives on the on‐going research are presented. The authors first discuss the wetting phenomenon on membrane surface, and then highlight the gradually evolved specially wettable system and its coupling with membrane materials. Next, relatively comprehensive preparation methods and applications of oil–water filtration membranes utilizing special wettability are summarized. Finally, the authors conclude the current achievements and challenges in specially wettable membranes for oil–water separation and outlook the future in this field. Abstract : Bioinspired special wettability has opened new possibilities to improve membranes and their performances in separation processes. This review offers a state‐of‐the‐art assessment of the latest research work on selective membrane materials under the concept of special wettability for highly efficient oil–water separation. Wetting phenomenon, special wettability in membranes, and comprehensive membrane preparation methods are presented.